What is known from the existing literature about adolescent knowledge and attitudes towards dementia and interventions to enhance this? A scoping review - Niamh McCarthy; Svea Nagel; Gabriel Vaughan; Emma Berry; Gillian Carter; Lisa Graham-Wisener (PLoS ONE, 2025)
Objectives Individuals with dementia often experience stigmatisation and social exclusion. To develop dementia-friendly communities, it is important to take a life-course approach to enhance the perception of dementia in the general population. Currently, we lack an overall understanding of adolescent perceptions of dementia. This scoping review is the first to identify the existing literature on the knowledge and attitudes held by adolescents (aged 10–19 years) towards dementia. Methods A JBI Scoping Review. Four bibliographic databases (MEDLINE, PsycINFO, EMBASE, and CINAHL) were searched to identify eligible studies. Eligibility criteria included qualitative and quantitative studies examining the knowledge and attitudes of adolescents (10–19-year-olds) towards dementia. Studies were screened for eligibility, with data extracted using JBI tools and synthesised in relation to i) knowledge and attitudes and ii) interventions. Results In total 21 publications were identified from the UK, Slovenia, the United States, Taiwan, Canada, Israel, South Africa, and South Korea. Ten of these studies included interventions. Overall, studies reported adolescents to have a relatively low level of objective knowledge about dementia. Conversely, attitudes towards dementia were largely reported to be neutral-positive. However, adolescents living with a relative with dementia often held predominantly negative attitudes towards the condition. Gender and having a family member living with dementia were important predictors of both knowledge and attitudes. Interventions to date are educational or intergenerational in focus and appear similarly effective in increasing attitudes and awareness towards dementia. Conclusions The current scoping review identified a small but emergent body of literature on adolescent knowledge and attitudes towards dementia. The synthesised findings indicate low objective knowledge to be a particularly useful target for intervention and alongside other findings, will be useful to inform future research, particularly the development of high-quality intervention studies.